Beyond frame analysis: Formal analysis and genre typology in the communication study of short-form environmental video messaging. Issue 1 (1st March 2021) - Vaughan, Hunter; Johns, Lisa
As connected platforms such as Twitter, Instagram and TikTok rise in popular use, communication strategies are forced to grow more condensed and to be transmitted primarily across digital screens. Online short-form video has consequently become a primary format for environmental communication, though research on digital communication remains largely limited to frame analysis and discussions of print and still images. Filling a need in current scholarship on environmental media and aiming to further bridge humanities and communication research, this article offers a model for assessing environmentally themed short-form videos that complements communication studies' focus on messaging rhetoric with humanities-based film and visual culture analytic tools for assessing the connotative aspect of aesthetic and narrative elements. Intending to offer an applicable framework for environmental messengers, we develop a genre system of short-form videos along cognitive and emotional axes that can be quantitatively identified according to formal practices, demonstrated through an examination of four environmental short-form videos.